Analisis Manajemen Keuangan Syariah Pada Usaha Coffe Janji Jiwa Kota Jambi - Meisy Risna Yeni; Miftah Miftah; Efni Anita (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This study aims to analyze Islamic Financial Management in the Promise Jiwa Coffee Business in Simpang IV Sipin Village, Jambi City. Sources of data used in this study are primary data through direct informants from the place to be studied, secondary data through documentation, interviews, and literature. While the technique of collecting through observation, interviews and documentation. The approach used is a qualitative approach.Based on the results of this study indicate that financial management that is applied to increase income is Planning which plans a strategic and spacious place for a sense of comfort to consumers, as well as opening many branches, especially in the city of Jambi, Organizing at Promise Jiwa coffee only wants a simple but strong organization, in increasing cooperation and optimizing income, Leading which is seen as friendly and firm to every employee, and finally Controlling which is strong enough to supervise every time facing problems that occur in the business place. The obstacles that affect financial management during the COVID-19 pandemic are the lack of reserve funds, increasingly fierce business competition, as well as the prolonged covid 19 and can experience losses in the life promise coffee business. And also as for the impact of income on the coffee business, this promise of the soul of the city of Jambi resulted in delays in employee salaries and reductions in employees. For this reason, one of the efforts of the Promise Jiwa coffee owner is to keep trying and praying and correcting mistakes that are not good in terms of financial management that have not been maximized.